The new hybrid clover variety Flamingo - M. N. Gripas'; E. G. Arzamasova; E. V. Popova; O. L. Onuchina (Аграрная наука Евро-Северо-Востока, 2016)
The article presents the results of breeding work (1999-2015) on creation of new tetraploid variety Flamingo of hybrid clover (Thrifolium hybridum L.). The variety Flamingo (breeding population SGPG-19) was creatied in North-East Agricultural Research Institute (Kirov) and Falenki Plant-Breeding Station (Kirov region) by polycross of eight best parental forms of various eco-geographical origin selected by OCS: variety Luzhanin (North-West Agricultural Research Institute "Belogorka"), selective number R-100 (V.K. Williams All-Russian Fodder Research Institute), perspective populations SGPG-9 (selection from variety Kurtsevskiy, Archangelsk region), SGPG-11 (variety Frida, Sweden), SGPG-12 (variety Pervenets from Moscow region), SGPG-13 (Priekulskiy tetra, Lithuania), SGPG-14, SGPG-15 (North-East Agricultural Research Institute), followed by recurrent biotipical selection. As a result of perennial (2007-2015) studying in competitive variety testing of North-East Agricultural Research Institute the new variety has the advantage on standard Fregat by basic economic-valuable traits. It is early-maturing (period from spring growth till first cutting is 54-62 days; till seeds ripening - 108-123 days); has high winter hardiness (75-90%), forage productivity of 8.75 t/ha of dry matter (+6.3% to standard), protein yield of 1.04 t/ha (+9.5% to standard), seed yield of 1.17 c/ha, root rot resistance (degree of defeat 0.1-1.8 points on a five-point scale). According to date of ecological varietal testing (2013) under agro-climatic conditions of Falenki Plant-Breeding Station differ from Kirov by poor soil fertility and contrasting weather conditions in the growing season the variety Flamingo significantly surpassed standard Fregat on protein yield (0.61 t/ha) by 8.9% at protein content in dry matter of 16.75% (+2.12% to standard). In 2015 the new variety of hybrid clover Flamingo transferred to the State variety testing as recommended for hay, pasture use, as well as for creation of melliferous fields in all areas of cultivation of the crop in the Russian Federation.